Effects of School Closure on Transmission of COVID-19. A Rapid Systematic Review - Muhammed, Zana Faris (Kurdistan Journal of Applied Research, 2020)
Globally school closure is one of the social distancing strategies used to mitigate transmission of pandemic novel corona virus (COVID-19) among school populations. However, there are uncertainties around when, how and for how long schools need to be closed. There is limited evidence for the impact of school closure on the number of cases and spread of COVID-19 to inform management of future outbreaks. Several databases were searched using an adapted search strategy to obtain studies that met the inclusion and exclusion criteria. A large number of studies were found and they were quality appraised. Eight good quality studies were identified and these were reviewed. The studies that contained the desired outcomes were three epidemiological studies, and five modeling studies using actual data that making assumptions about changes in transmission dynamics after school closure is applied. The results show that schools were closed for different timings related to the peak epidemics. School closure almost reduced the transmission of the COVID-19. Delay in closing schools and combinations with other control and management measures may affect the likelihood of drawing consistent conclusions about the effectiveness of school closure on COVID-19.